2019
DOI: 10.1155/2019/9403295
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Crossover Pilot Study of Telemedicine Delivered via iPads in Parkinson’s Disease

Abstract: Background We investigated the feasibility and safety of a video-based telemedicine system, delivered via a tablet, in Parkinson's disease (PD). Methods In a randomized, crossover, open-label pilot trial, we compared a telemedicine period (regular visits every two months with intermediate video calls via an iPad mini) with a control period (regular visits every two months), both lasting 6 months. We included 10 patients diagnosed with PD according to the British Brain Bank criteria, aged 20–75 years. The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 30 publications
(41 reference statements)
0
46
0
Order By: Relevance
“…20,21 Patients ized study showed that a telemedicine system delivered via a tablet could successfully be used by PD patients as a part of their care. 23 Thus, it is possible to have a medical examination at home or even in a nursing home. As for PD-related symptoms, for example, facial expressions, speech, presence of tremor, and bradykinesia can be evaluated visually, and lower limb, trunk, and gait symptoms can be evaluated during the interview.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Patients ized study showed that a telemedicine system delivered via a tablet could successfully be used by PD patients as a part of their care. 23 Thus, it is possible to have a medical examination at home or even in a nursing home. As for PD-related symptoms, for example, facial expressions, speech, presence of tremor, and bradykinesia can be evaluated visually, and lower limb, trunk, and gait symptoms can be evaluated during the interview.…”
Section: Discussionmentioning
confidence: 99%
“…Our intention was to implement a virtual admission for patients in need of intensive monitoring and prompt adjustment of treatment. Previous studies investigating telemedicine for PD patients were focused on single interactions comparable to outpatient clinic appointments [1][2][3]. To the best of our knowledge, there are no other studies employing telemedicine as a "virtual admission.…”
Section: Dear Editormentioning
confidence: 99%
“…Their results were mostly promising and well evaluated by doctors and patients 92 . In a cross-over study using a tablet for teleconsultations compared with regular consultations, PD patients had similar Unified Parkinson's Disease Scale (UPDRS) and Hoen and Yahr (H&Y) scales 93 . A small clinical trial with PD patients observed better outcomes in quality of life and UPDRS than those observed after regular consultations 94 .…”
Section: Movement Disordersmentioning
confidence: 99%